AGROWISATA AGROWISATA IKAN JELAWAT DI KOTA SAMPIT - Lesmana, Dewina Maharani; Sutrisno, Herwin; Susi, Theresia (JURNAL PERSPEKTIF ARSITEKTUR, 2023)
Abstract : Sampit city has a strategic position in the trade route that is flowed by a large river, the Mentaya River, has a lot of diversity of freshwater fauna, one of which is the Jelawat fish. Jelawat fish that are found in the Mentaya River make this Jelawat Fish an icon of Sampit city that can be seen along the 2 km jalan Tjilik Riwut corridor and Jelawat fish monument in an open space near the Sampit City Port Dock. The purpose of Jelawat fish agrotourism design is to optimize the potential of the existing site with a symbolic architectural approach. The method used basic linear design method. The design results show that the Jelawat fish agro-tourism area in Sampit City can accommodate activities related to Jelawat fish as educational activities for the introduction of types of freshwater fauna in the Mentaya River and processed Jelawat fish into culinary or souvenirs, and interacting with fellow visitors and animals in the area. The building, which is designed with a symbolic architectural approach, is intended to be an icon of the area in Sampit city related to Jelawat fish.